The Influence Of Corporate Brand And Brand Image On Consumer Decisions To Become Home Ownership Credit Customers State Savings Bank - Harta, Feri Suheri; Hadi, Prasetyo; Manggabarani, Alfatih S (UNIVERSITAS PAKUAN, 2019)
This study analyzes the impact of corporate brand and brand image on the purchasing decisions of Bank Tabungan Negara's (BTN) Home Ownership Loan (KPR) products using the SmartPLS 3.2.9 method. The results indicate that both corporate brand and brand image significantly influence purchasing decisions. Corporate brand contributes directly and also influences through brand image. The research, based on 110 respondents who completed the questionnaire, provides in-depth insights into the factors affecting consumer decisions in choosing BTN's KPR products. These findings highlight the importance of building and managing a strong corporate brand and brand image to enhance product attractiveness in the market.